Comparison of soil active organic carbon fractions in different vegetation zones in purple-soil of hill slope - Yang, Manyuan; Yang, Ning (Bangladesh Journal of Botany, 2020)
To explore the effect of vegetation restoration on soil carbon cycle and fractions of soil organic carbon pool on purple-soil hill slope in Hengyang City of Hunan Province, China was selected. The soil samples of 0 - 10 and 10 - 20 cm soil layers under three types of vegetation, i.e., grassland zone (GZ), grassland-forest zone (GFZ) and forest zone (FZ). The dynamics of soil active organic carbon (SAOC) fractions to provide theory basis for the influence of soil carbon cycle and different vegetation zones on the fractions of organic carbon pool and its stability. Results show: Microbial biomass carbon and easily oxidizable organic carbon exhibited a decreasing pattern: FZ, GZ, GFZ (p < 0.05); Dissolved organic carbon exhibited a decreasing pattern: FZ, GFZ, GZ (p < 0.05); Light fraction organic carbon was the highest in FZ (p < 0.05), and the second in GZ and GFZ; The availability of active organic carbon in 0 - 10 cm soil layer was higher than that of 10 - 20 cm soil layer (p < 0.05); In comparison with GFZ, the herb in GZ could increase the contents of active organic carbon.